Ultrafine NiMoOx nanoparticles confined in mesoporous carbon for the reduction of nitroarenes: effect of the composition and accessibility of the active sites. Issue 8 (6th February 2019) - Li, Shuna; Lv, Yipin; Song, Guolong; Li, Cuncheng; Gao, Daowei; Chen, Guozhu
Abstract : Ultrafine NiMoO x NPs were confined in the framework of mesoporous carbon by using the replication method for the reduction of nitroarenes. Abstract : The design of ultrafine NiMoO x nanoparticles (NPs) confined in hierarchically porous carbon remains a great challenge due to its high calcination temperature. In addition, the composition of active sites of NiMoO x NPs for the hydrogenation reaction is still ambiguous. Herein, we report a general approach for the synthesis of ultrafine NiMoO x NPs confined in mesoporous carbon with different morphologies and compositions using the replication method with SBA-15 as a hard template. The pore structure of mesoporous carbon and the Ni/Mo composition valence-state were discovered to be the main factors in the reduction of nitroarenes. The NiMoO x /mesoporous carbon-platelet (NiMoO x /MC-PL) with short mesochannels (∼350 nm) and high surface area (∼995 m 2 g −1 ) possessed excellent catalytic activity towards the reduction of 4-nitrophenol, whereas NiMoO x /mesoporous carbon-hexagonal-prism (NiMoO x /MC-HP), NiMoO x /mesoporous carbon-long-rod (NiMoO x /MC-LR), and NiMoO x /mesoporous carbon-spherical (NiMoO x /MC-SP) with long mesochannels and relatively less surface area exhibited poor catalytic performance. The bifunctional mechanism or electronic synergistic effects of Ni and Mo species enhanced their catalytic performance. A good balance between MoO x and metallic Ni (NiMoO x /MC-PL-450) was found to be suitable for the reduction of 4-NP.